Influence of chemical models on heat flux for EXPERT and Orion capsules. (May 2014) - Morsa, Luigi; Zuppardi, Gennaro; Votta, Raffaele; Schettino, Antonio
The computation of heat flux on two current re-entry capsules, European eXPErimental Reentry Testbed (EXPERT) and Orion, has been carried out by a direct simulation Monte Carlo code (DS2V) and by a computational fluid dynamic code (H3NS) in transitional regime, considering both non-reactive and fully catalytic surface. These capsules have been chosen for this analysis because they have been characterized by completely different shapes and re-entry trajectories. DS2V and H3NS use the Gupta and the Park chemical models, respectively. The results showed that the heat flux predicted by DS2V is always higher than that predicted by H3NS. Therefore, a sensitivity analysis of the chemical models on the heat flux has been carried out for both capsules. More specifically, the Park model has been implemented in DS2V as well. The results showed that DS2V and H3NS compute a different chemical composition both in the flow field and on the surface, even when using the same chemical model (Park); therefore, the different results obtained from the two codes can be attributed mostly to the different methodology used in handling all chemical processes.